Static and dynamic balances of patients with acromegaly and impact of exercise on balance - ÇAMLIGÜNEY, ASİYE FİLİZ; ERKUT, AYŞE OYA; ÇOTUK, HASAN BİROL (SPRINGER, 2019)
Purpose Patients with acromegaly may have balance abnormalities due to changes in body composition. We aim to compare static and dynamic balances in patients with acromegaly and healthy volunteers, and to evaluate the effects of exercise on balance in patients with acromegaly. Methods This prospective study included 25 patients with acromegaly followed at endocrinology clinic of Cerrahpasa Medical Faculty and 13 healthy volunteers. The acromegalic patients were divided into 2 groups. Group A (n = 11) attended an exercise program 3 days/week for 3 months, whereas group B (n = 14) and healthy volunteers (Group C) were exercise-free. Bipedal and unipedal stance static and dynamic balance tests were performed using a Prokin 252N device. Results The ages, demographic characteristics, and body compositions were similar. In acromegalic patients, the static balance parameters of displacement of center-of-pressure in anterior-posterior direction (C.o.P.Y) while eyes open (p = 0.002) and on left leg (p = 0.001), in left-right direction (C.o.P.X) on right leg (p = 0.03), eyes-closed average medio-lateral velocity (AMLV) (p = 0.001) and the dynamic parameter of forward/backward front/right standard deviation (FBFRSD) (p = 0.02) were significantly different from healthy controls. When the exercise effect on balance was evaluated between group A and B, there were significant improvements in most parameters of dynamic balance measurements of both forward-backward and medial-lateral sway (FBFRSD, FBDME, and RLBLSD) (p = 0.02, p = 0.02, and p = 0.004, respectively) after exercise in group A. Conclusions Patients with acromegaly had impairments at various static and dynamic balance parameters, especially in posterior direction. After a 3-month exercise program, the dynamic balance profoundly improved, but static balance was relatively preserved in patients with acromegaly.
Keywords: Acromegaly; Dynamic balance; Exercise; Static balance; QUALITY-OF-LIFE; ANKYLOSING-SPONDYLITIS; POSTURAL CONTROL; MUSCLE STRENGTH; REHABILITATION; RELIABILITY; PERFORMANCE; STABILITY; HEALTHY